2017
DOI: 10.5539/jas.v9n13p50
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Properties, Total Phenolic and Antioxidant Activity of Mixed Tropical Fruit Juice, TP 3 in 1TM

Abstract: This study was carried out on the TP 3 in 1 TM juice formulation, which consisted of pomegranate concentrate with guava and roselle extract. This study aimed to determine its physicochemical properties, proximate content, total phenolic content, antioxidant activity, total sugar, vitamin C and several targeted polyphenol compounds. Total phenol content was determined using Folin-Ciocalteu method while antioxidant activity was determined using DPPH and ABTS methods. The results showed pH and total soluble solid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
(40 reference statements)
0
1
0
1
Order By: Relevance
“…In our previous work, we successfully developed a tropical fruit juice mixture that consisted of pomegranate concentrate with guava and roselle extracts, and reported its high polyphenolic contents and antioxidant capacity (Abdul Malek et al, 2017;Ooi et al, 2020). The polyphenols abundant in the juice mixture were ellagic acid, gallic acid, catechin, epicatechin, p-coumaric acid, chlorogenic acid, procyanidin B 2 , and kuromanin chloride (Abdul Malek et al, 2017). In the present work, we used the same formulation of the juice mixture to investigate its protective capacity and abrogating effect on the mutagenicity of MMS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous work, we successfully developed a tropical fruit juice mixture that consisted of pomegranate concentrate with guava and roselle extracts, and reported its high polyphenolic contents and antioxidant capacity (Abdul Malek et al, 2017;Ooi et al, 2020). The polyphenols abundant in the juice mixture were ellagic acid, gallic acid, catechin, epicatechin, p-coumaric acid, chlorogenic acid, procyanidin B 2 , and kuromanin chloride (Abdul Malek et al, 2017). In the present work, we used the same formulation of the juice mixture to investigate its protective capacity and abrogating effect on the mutagenicity of MMS.…”
Section: Discussionmentioning
confidence: 99%
“…Tropical fruits, such as pomegranate (Punica granatum L.), guava (Psidium guajava L.), and roselle (Hibiscus sabdariffa L.) have high phenolic contents and potent antioxidant activities (Jiménez-Escrig et al, 2001;Wu et al, 2018;Fahmy et al, 2020). Pomegranate, guava, and roselle juices individually contain various phytochemical contents, and their combination may provide beneficial activity towards health (Abdul Malek et al, 2017). A previous study reported that tropical fruit juice mixture consisting of pomegranate concentrate with guava and roselle extract protected Wistar male rats from βamyloid-induced brain tissue damage in the CA1 region of the hippocampus (Ooi et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Previous in vitro study on the mixed concentrated juice consisted of pomegranate, dates and honey combination showed that these functional foods in combination contained high antioxidant content and it is suggested to consume this juice as a supplement 107 . Another study on different functional mixed fruit juice of pomegranate, guava and roselle in combination, also contained high total phenolic content and antioxidant activity 108 . These showed that these functional foods in combination may have potential to manage various diseases especially for diseases that have oxidative stress as its prevalent process to cause diseases.…”
Section: Potential Of Functional Foods Combination To Treat Various D...mentioning
confidence: 93%
“…Los polifenoles son un grupo de compuestos que comúnmente se encuentran en grandes cantidades en las plantas como sus metabolitos secundarios, de igual manera estos son conocidos por sus propiedades antioxidantes (Malek et al, 2017) y antibacterianas. Los polifenoles se clasifican comúnmente en cuatro grupos principales; flavonoides, ácidos fenólicos, lignanos y estilbenos (Acosta, 2019).…”
Section: Introductionunclassified